Profile of Critical Thinking Skills and Sustainability Awareness of Junior High School Students in Dumai City - Andriansyah, M; Pursitasari, Indarini Dwi (Universitas Negeri Yogyakarta, 2025)
Critical thinking skills and sustainability awareness are important competencies for students in facing 21st century education as well as supporting the achievement of Sustainable Development Goals (SDGs). This study aims to describe the profile of critical thinking skills and sustainability awareness of junior high school students in Dumai City, using an explanatory sequential design. Data collection involved critical thinking tests, sustainability awareness questionnaires, and interviews with teachers. The results of this study show that students critical thinking skills are in the low to very low category, while students’ sustainability awareness shows a medium category in the practical aspect, but low in the behavioral and emotional aspects. This research provides important recommendations to support the development of education that integrates critical thinking exercises and sustainability education through an evidence-based approach. Sustainability awareness shows a mixed profile: moderate in the practical dimension—students can name everyday actions such as waste sorting and water conservation—yet low in behavioral and emotional dimensions, signaling limited persistence of pro-sustainability habits and weak affective commitment. These results suggest a gap between knowing and doing that schools can address through evidence-based curriculum and pedagogy.